Does flexibility exercise affect running economy? A brief review - Carter, J.; Greenwood, M. (Strength and Conditioning Journal, 2015)
A critical component of running performance is running economy (re). Some factors that determine re are unable to be changed through training, whereas other components of re can be altered through exercise, with other re factors being less modifiable through training. The effect of flexibility (flx) on re is less researched and not well understood. The purpose of this article is to explain re, discuss if a correlation exists between flx and re, examine if acute stretching (str) affects re, review if chronic str affects re, and provide concluding statements on the effects of flx and str on re.